2003
DOI: 10.1111/j.1502-3885.2003.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale glaciotectonic deformation in the Great Lakes basin, USA‐Canada

Abstract: Investigation of the sedimentology, stratigraphy and deformation structures of an exposed sedimentary sequence associated with an isolated large ridge along the eastern shore of Lake Michigan reveals that it is part of a broad grounding‐line fan complex that was subjected to extensive glaciotectonic deformation. It is concluded that the sequence formed following melting back of the margin of the Lake Michigan lobe and was subsequently overridden and deformed during advance of the ice margin probably to the Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…The southern margin of the Laurentide Ice Sheet was likely covered by permafrost during the Last Glacial Maximum (LGM) [ Cutler et al , 2000] (purple areas in Figure 1). There is little evidence of permafrost, however, in the Great Lakes basins, likely because these low‐lying areas were covered by proglacial lakes [ Larson et al , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The southern margin of the Laurentide Ice Sheet was likely covered by permafrost during the Last Glacial Maximum (LGM) [ Cutler et al , 2000] (purple areas in Figure 1). There is little evidence of permafrost, however, in the Great Lakes basins, likely because these low‐lying areas were covered by proglacial lakes [ Larson et al , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Although primary sedimentary structures pre-dating the deformation are present in most of the folded units, they are largely absent in the center of the narrow anticlinal structures. Although Larson et al (2003) observed that crests of the anticlines trend east-northeast and appear to form wall-like bodies that separate several broad structural depressions, it is currently unknown whether the deformation structures observed in the outcrop are isolated or continuous features, and if the latter, what is the length and orientation.…”
Section: Cst Characterization Of Large-scale Glaciotectonic Deformationmentioning
confidence: 96%
“…The work presented here focuses on an area known as the Ludington Ridge, south of the town of Ludington, Michigan, where Larson et al (2003) described several large-scale deformation structures in a steep cliff bordering Lake Michigan. Throughout the Ludington ridge, and particularly in the cliff area, springs and gullies indicate a preferred pattern of groundwater drainage and past landslides related to this deformation.…”
Section: Cst Characterization Of Large-scale Glaciotectonic Deformationmentioning
confidence: 99%
See 1 more Smart Citation